IMPACT OF ECOLOGICAL EXPLORATION PROCESSES ON THE DEVELOPMENT OF SCIENTIFIC INVESTIGATION APPROACH (DIS) AND PERSONAL ACTION PROJECTS AMONG HIGH SCHOOL STUDENTS: A TOOL FOR REFLECTION ON CLASSROOM PRACTICES CASE OF AN ECOLOGICAL SCHOOL TRIP IN A NATURAL E - Hafer, Redouane; Tridane, Malika; Belaaouad, Said (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The teaching of SVT in general offers learners an environment that allows them to explore and explain natural phenomena, to understand different spatio-temporal scales, to understand the world around them so that they can decide and act responsibly. It is interesting to note that the scientific ecological outing (SES) is an integral part of the SVT teaching program, at both college and qualifying secondary level, and that teachers are called to organize these outings in agreement with the programs as recalled by the circulars of the MEN. However, the SES allows the real observation and the execution of experiential practices in the field, it is the opportunity to place the learner in a learning situation according to a reflective and investigative scientific approach from his confrontation with reality [8] [9]. Offers a didactic framework and formalizes evaluation criteria for the implementation and management of a scientific investigation process. So that he can make connections with what the learner acquires as abstract knowledge in class in order to be able to decide and act responsibly and critically on the scale of everyday situations as an Eco citizen.